Pengaruh Varietas dan Dosis Pupuk Kalium terhadap Perkembangan Penyakit Bulai (Peronosclerospora maydis Rac.Saw), Pertumbuhan dan Produksi Jagung - Habibi, Ach.; Nurcahyanti, Suhartiningsih Dwi; Majid, Abdul (Jurnal Agro Teknologi Tropika, 2017)
Downy mildew is one of the important diseases in maize. This disease has spread in Indonesia, even in certain areas downy mildew is already endemic. Downy mildew can cause crop failure, especially when damaging corn crops susceptible varieties and at a young age. The research objective was to determine the effect of the three varieties of corn and potash fertilizers to the development of downy mildew, plant height, number of leaves, and corn production. This research was conducted at the home of wire, Dukuhsia Rambigundam Rambipuji District of Jember, in March to June 2016. This study was onducted by completely randomized design (CRD) factorial consist of two factors, the first factor was the maize varieties, consists of 3 levels: Asian Honey (V1), Pioneer-21 (V2), Pacific 339 (V3). The second factor was the dose of fertilizer which consists of 4 levels: K0 (without fertilizer), K1 (1 gram/plant), K2 (2 gram/plant), K3 (3 gram/plant). Asian maize varieties Honey and potassium fertilizer dose of 3 grams / plant respectively indicate the best treatment in suppressing the development of downy mildew, growth and production of maize.